Protective Mechanisms of Butyrate on Inflammatory Bowel Disease - Silva, João P.B.; Navegantes-Lima, Kely C.; Oliveira, Ana L.B.; Rodrigues, Dávila V.S.; Gaspar, Sílvia L.F.; Monteiro, Valter V.S.; Moura, Davi P.; Monteiro, Marta C. (Current Pharmaceutical Design, 2018)
Inflammatory bowel disease (IBD) is a multifactorial chronic disease, commonly associated with alteration in the composition and function of gut microbiota. This process can lead to a decreased production of short chain fatty acids (SCFAs) by the gut microbiota, mainly butyrate, which is an important immunomodulatory molecule in the intestine. Butyrogenic bacteria normally produces butyrate through carbohydrate fermentation or amino acids degradation pathways. This molecule plays an important protective role in intestinal homeostasis acting in both adaptive immunity and innate immunity. This review summarizes the current knowledge about the role of butyrate on the development of IBD and the protective mechanisms of this metabolite on the intestinal mucosa and the whole body, as reported by in vitro and in vivo studies. Thus, butyrate can regulate the activation of regulatory T cells, increasing the acetylation of histones and decreasing the activation of NF-ΚB. In addition, it can also stimulate the mucus production from epithelial cells and the rearrangement of tight junction proteins.
Keywords: IBD